Fluxes of Dissolved Inorganic Nutrients and Suspended Sediment at The Trat River Mouth, Trat Province in 2018 - Meesub, Benjamas; Buranapratheprat, Anukul; Thaipichitburapa, Patrawut; Kan-atireklarp, Suthida; Kan-atireklarp, Supawat (Burapha Science Journal, 2026)
This research aims to study fluxes of dissolved inorganic nutrients and suspended sediment at the Trat River mouth for 6 times of the year 2018. The results showed that the net fluxes of water, dissolved inorganic ammonia, nitrite, nitrate, phosphate and silicate in February, April, June, August and October were directed seaward except in December that the net fluxes of water, dissolved inorganic, nitrite, nitrate, phosphate and silicate were directed riverward. Suspended sediment fluxes in February, April and December were directed riverward while those in June, August and October were directed seaward. All dissolved inorganic nutrient concentrations (except phosphate and suspended sediment) increase proportionally to the amount of discharge. The annual average of the net fluxes of water, ammonia, nitrite, nitrate, phosphate, silicate and suspended sediment were 5.81 x 106 m3/day, 985.52 Kg N/day, 26.57 Kg N/day, 1,205.42 Kg N/day, 128.15 Kg P/day, 17,845.25 Kg Si/day and128.98 ton/day, respectively. Compared with data in 2013, fluxes of all nutrients showed increasing trend during both dry and wet seasons, just fluxes of nitrite and nitrate showed increasing trend only in dry season. All fluxes were directed seaward. Water qualities of the Trat river mouth was evaluated within the standard as surface water classification type 3 (water quality for agriculture).